2005
DOI: 10.1080/00365520510023260
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endoscopically negative and positive gastroesophageal reflux disease in the Japanese

Abstract: The prevalence of GERD in the Japanese was 17.9% and the prevalence rates of NERD and erosive esophagitis were 10.9% and 8.6%, respectively. The majority of symptomatic patients did not have endoscopically proven esophagitis. Hiatal hernia is the only important predictor of the presence of GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
144
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 27 publications
15
144
5
Order By: Relevance
“…GERD is influenced by multiple factors, including gastric acid secretion, hiatal hernia, the lower esophageal sphincter function, esophageal motility, esophageal perception and others (1,(3)(4)(5)28). The prevalence of GERD has increased among Asian populations in recent decades, and the increment in the rate of GERD in Asians is thought to be caused by several factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GERD is influenced by multiple factors, including gastric acid secretion, hiatal hernia, the lower esophageal sphincter function, esophageal motility, esophageal perception and others (1,(3)(4)(5)28). The prevalence of GERD has increased among Asian populations in recent decades, and the increment in the rate of GERD in Asians is thought to be caused by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…GERD has been becoming more prevalent in Asian populations in recent decades, and although the disease is considered to be a common disorder in both Western and Asian populations, its increasing prevalence in Asia may be due to multiple factors, such as the Westernization of eating habits, decrease in the rate of Helicobacter pylori infection, increased gastric acid secretion and a larger elderly population, as well as other factors (2)(3)(4)(5)(6)(7)(8)(9). High intra-abdominal pressure caused by abdominal fat accumulation has been demonstrated to increase the gastroesophageal pressure gradient and incidence of gastroesophageal reflux, while obesity and a high body mass index (BMI) have repeatedly been reported to be correlated with a high prevalence of reflux esophagitis and symptoms of GERD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…7 Interestingly, there is a male-predominant sex difference through the spectrum of reflux esophagitis, BE, and EAC. [7][8][9] In addition, the male to female ratios become higher with more progression towards EAC. 7 Meanwhile, reflux symptoms and NERD generally affect more women than men.…”
Section: Introductionmentioning
confidence: 99%
“…7 Meanwhile, reflux symptoms and NERD generally affect more women than men. 7,9 Epidemiological data have suggested that the esophageal mucosal epithelium is more fragile to refluxed gastroduodenal contents in men compared to that of women, 7,10 although women are more susceptible to GERD symptoms than men. Sex means a human's biological status based on their reproductive systems and functions assigned by chromosomal type.…”
Section: Introductionmentioning
confidence: 99%
“…14 Relying upon endoscopic examination and the presence of GERD symptoms, a Japanese study found a 17.9 % GERD prevalence in the adult population, among which 7.1 % were diagnosed with esophagitis and 10.8% not. 26 Regarding the consumption of beverages causing erosion, coffee (58.2%), carbonized drinks (57%), tea (24.1%) and, to a lesser extent, fruit juice (13.9%), soft drinks (13.9%) and energy drinks (3.8%) were relevant in the present study. The tooth surface examination has shown that in case of extrinsic and intrinsic acidic effects, mainly frontal and molar teeth featured enamel alterations, on the occlusal surface, as well as on the buccal tooth neck areas, mainly on the mandible.…”
Section: Discussionmentioning
confidence: 96%